What is the value for the ratio (a^2 + 2b^2)/ab if the value of the ratio a/b = 2sqrt3

neela | Student

To find (a^2+2b^2)/ab


If a/b = x, the a = bx.

Then (a^2+2b^2b^2)/ab =[ (bx)^2+2b^2]/(bx)b








However, if you write, the the given expression,(a^2 + 2b^2)/ab, like (a^2 + 2b^2)/(ab), then

(a^2+2b^2)/(ab) =[(bx)^2+2b^2]/(bx*b)

=b^2(x^2+2)/(b^2 *x) =(x^2+2)/x = 7(sqrt3)/3



krishna-agrawala | Student

We have to find value of expression E = (a^2 + 2b^2)/ab

given a/b = 2*3^1/2.

We firsts simplify the given expression as indicated in following steps.

E = (a^2 + 2b^2)/ab

= (a^2)/ab + (2b^2)/ab

= a/b + 2/(a/b)

Substituting given value of a/b in this expression we get:

E = 2*3^1/2 + 2/(2*3^1/2)

= 2*3^1/2 + 1/(3^1/2)

= (3^1/2)*(2 + 1/3)

= (3^1/2)*(7/3)

= 7/(3^1/2)

giorgiana1976 | Student

For calculating the expression, we’ll choose to express “a”depending on “b”,

So, from the given facts of the problem, we know that:


We’ll cross multiply and  we’ll have:

a=2*b*sqrt3 => a^2 =4*b^2*3 => a^2 =12*b^2

Now we’ll substitute a and a^2 in the expression which has to be calculated:

E(a,b)=(a^2 + 2*b^2)/a*b= (12*b^2 + 2*b^2)/2*b^2*sqrt3

We’ve noticed that the expression in a and b, have been transformed into an expression depending only by “b”.


 After reducing the similar terms:


We’ll amplify  with sqrt3, in order not to keep a "sqrt" to the denominator, which is not indicated.